Polyvalence of an Open Plan Apartment - Characteristics and Spatial Organization Principles - Alfirević, Đorđe; Simonović Alfirević, Sanja (Arhitektura i urbanizam, 2022)
Polyvalence (gr. poly multi, nlat. valentia value - multivalued, ambiguous, multipurpose) is a term that has a wide range of uses in science and art. Polyvalence usually implies different ways (regimes) of using the same space, ie. adaptability of space to different human needs with minimal physical modifications. It is a well-established opinion in science that the term polyvalence in architecture primarily refers to the level of an entire apartment or house, ie. on the possibility of reorganization of the internal structure (conversion of premises), which can be viewed as a broader interpretation of the term. On the other hand, there is a narrower interpretation, which refers to the polyvalence of a part of an apartment, a space or a room, ie. on the possibility of overlapping housing functions at different times in the same space, the so-called. open plan. The subject of this research are polyvalent open-plan apartments, in which several housing functions are combined in the same space. The aim of the research is to investigate the most significant characteristics and principles of spatial organization that are relevant for polyvalent open spaces with an open plan, through a scientific analysis of reference sources, interpretations and characteristic examples. Also, the paper will re-examine the view that ideal polyvalence is a borderline form of organization of polyvalent space, in which each part of the surface when changing the position of functions has some use value.